Case-Based Reasoning Research and Development 21st International Conference, ICCBR 2013, Saratoga Springs, NY, USA, July 8-11, 2013, Proceedings - Delany, Sarah Jane; Ontañon, Santiago (Lecture Notes in Artificial Intelligence,, 2013)
This book constitutes the refereed proceedings of the 21st International Conference on Case-Based Reasoning Research and Development (ICCBR 2013) held in Saratoga Springs, NY, USA, in July 2013. The 17 revised full papers presented together with 9 posters were carefully reviewed and selected from 39 submissions. The presentations and posters covered a wide range of CBR topics of interest both to researchers and practitioners including case retrieval and adaptation, similarity assessment, case base maintenance, knowledge management, recommender systems, multiagent systems, textual CBR, and applications to healthcare and computer games.